Pendapatan dan Kesejahteraan Petani Padi di Kawasan KP2B Kecamatan Abung Timur Kabupaten Lampung Utara - Haros, Saskia Susanti; Affandi, Muhammad Irfan; Murniati, Ktut (Universitas Galuh, 2025)
The increasing conversion of agricultural land, especially rice fields, has become a particular concern for the government considering rice as the staple food of the community. Based on this, the government is striving to minimize land conversion by establishing sustainable food agricultural protection areas (KP2B), as rice fields have the potential to improve farmers' welfare. This study aims to analyze the income from rice farming, the income of rice farming households, and the welfare level of rice farming households in Merbau Mataram District, South Lampung Regency. This research uses a survey method. The research location was deliberately chosen in the Abung Timur District, North Lampung Regency, as one of the districts with the largest rice harvest area in North Lampung Regency and is a KP2B area. The respondents in this study are rice farmers. The selection of respondents, 75 rice farmers, used a random sampling technique (system random sampling). The data analysis used includes income analysis, R/C, and household welfare analysis based on the criteria of Sajogyo (1997), BPS (2014), and expenditure share. The research results indicate that the income from rice farming in the sustainable food agriculture area (KP2B) in the Abung Timur District, with a land area of 0.56 ha, amounts to Rp 29,297,079.20 per year. Rice farming is a profitable and viable business unit with an R/C value of 3.49. Meanwhile, the income of rice farmer households in the sustainable food agriculture area (KP2B) in Abung Timur District amounts to Rp 48,016,257.28 per year. The share of income from total rice farming (on-farm) is 61.01 percent, income from outside rice farming (off-farm) is 17.93 percent, and non-agricultural income (non-farm) is 21.05 percent. Based on the welfare classification by Sajogyo, the Central Statistics Agency 2014, and the expenditure share of the welfare level of rice farmers in the sustainable food agriculture area (KP2B) of Abung Timur District, they are classified as prosperous.